The Influence of Price Perception and Customer Satisfaction on Customer Loyalty - Maulana, Alfian Zidane; Pasha, Fajar Azzam; Sukendar, Hendrik Basguni (Golden Ratio of Data in Summary, 2025)
The purpose of this study is to analyze the influence of price perception and customer satisfaction on customer loyalty among Go-jek service users in Jatimakmur. This research employs a quantitative approach using a survey method and questionnaires distributed to 154 respondents who are Go-jek users in Jatimakmur, with data analysis conducted through descriptive statistics and multiple linear regression. The independent variables used in this study are price perception and customer satisfaction, while the dependent variable is customer loyalty. The results of the study show that both price perception and customer satisfaction have a positive and significant effect on customer loyalty, both simultaneously and partially. This is indicated by the t-table > t-calculated for price perception (4.401 > 1.975) and customer satisfaction (4.009 > 1.975). Based on the F-test, price perception and customer satisfaction simultaneously have a significant effect on customer loyalty. This is shown by an F-calculated value of 51.210, which is greater than the F-table value of 3.06, and a significance value of 0.000, which is less than 0.050. Meanwhile, the adjusted R2 coefficient is 0.381, meaning that price perception and customer satisfaction can explain 38.1% of the customer loyalty variable, while the remaining 62.9% is influenced by other factors not included in this study.